NOD2 Mutation-Associated Case with Blau Syndrome Triggered by BCG Vaccination - Akiko Arakawa; Naotomo Kambe; Ryuta Nishikomori; Akiyo Tanabe; Masamichi Ueda; Chikako Nishigori; Yoshiki Miyachi; Nobuo Kanazawa (MDPI AG, 2021)
We describe a patient who developed multiple granulomatous skin lesions after Bacille de Calmette et Guérin (BCG) vaccination without significant effect by topical corticosteroid, followed by painless cystic tumors on the bilateral knees and hands and inflammatory changes on ophthalmologic examination. A functional mutation in NOD2 was detected by a genetic analysis, and he was diagnosed as sporadic Blau syndrome. Since NOD2 acts as a sensor for the BCG component, it is possible that BCG vaccination may trigger granuloma formation in Blau syndrome patients with such genetic background.